Does leadership style still affect employee performance in the Millennium era? - Srimulatsih, Mahbubah (International Journal of Islamic Business and Management Review, 2022)
This study aims to determine the effect of leadership style on employee performance in the current digital era. In this study, sampling using a saturated sample technique that is equal to 32 people or the entire population is sampled. The results showed that the t-count value was 6.554 while the t_table value was 2.00488 so it can be explained that the t_count value (6.170) > from t_table (2.04227) so it can be concluded that there is a significant influence between leadership style on employee performance in the digital era when this. This research proves that until now the leadership style is still effective to encourage better performance at all levels.